A Literature Review on the Risks of Drug and Substance Abuse among Students, Youth and Adolescents (African Multidisciplinary Journal of Research, 2025)
The escalating prevalence of substance abuse encompassing alcohol, nicotine (e.g., vaping), cannabis, and "study drugs" like amphetamines among high school and university students undermines the mission of educational institutions. This behavior correlates with immediate risks like overdose and long-term deficits in cognitive function, academic achievement, and psychosocial development, highlighting an urgent need for evidence-based interventions. This review evaluates empirical evidence on the prevalence, patterns, and impacts of substance use among adolescents and youth. A systematic, PRISMA-guided search was conducted across global (PubMed, PsycINFO, Web of Science) and regional databases (AJOL, LILACS, SciELO, IndMED). Eligible studies sampled individuals aged 15–35 within secondary or tertiary educational environments and used validated measures and inferential statistics. From the 63 retrieved papers, 48 met the inclusion criteria. Findings reveal the most researched outcome is substance use abuse itself (51%, n=19), followed by academic performance (19%, n=7) and mental health (19%, n=7). Behavioral problems are the least examined (11%, n=4). Geographically, Nigeria and the United States contribute the most studies on prevalence, whereas Kenya leads research on academic impacts, South Africa on mental health, and India on behavioral outcomes. The most utilized theoretical frameworks are Social Learning Theory (peer influence, 14 studies), the Self-Medication Hypothesis (coping with distress, 9 studies), and Cognitive Load Theory (academic impairment, 6 studies). The primary focus is on secondary and university students, particularly adolescents aged 15–19, reflecting early experimentation. Marginalized groups, youth, refugees, and street children are severely underrepresented. Key gaps include a theoretical overreliance on narrow behavioral frameworks, neglecting broader sociocultural perspectives. Empirically, rural and marginalized populations remain underexplored. Methodologically, cross-sectional self-report designs dominate, with limited use of multi-outcome models. Future research must employ longitudinal and experimental designs, use advanced analytics (e.g., SEM, machine learning), and intentionally recruit diverse subgroups within educational settings to understand heterogeneity in risk patterns. Culturally adapted measures, resilience frameworks, and digital prevention innovations are needed to strengthen interventions. These priorities align with policy shifts, like Kenya’s NACADA strategy, toward prevention, stricter regulation, and community-based approaches.